FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP MOTIVASI AUDITOR (Studi Empiris Pada KAP di Jawa Tengah - Wika Ariestya S., 10.05.52.0117; Badjuri, Achmad (Students Journal of Accounting and Banking, 2014)
This study aims to analyze empirically the factors that affect the motivation of auditors on KAP Central Java.The population in this study were all auditors working in the public accounting firm in Central Java. Sampling was done using purposive sampling method and sample size were 62 respondents. The primary data collection method used was a questionnaire method. Data were analyzed using multiple linier regression model.The result showed that the audit fee, competence, organizational commitment, professional commitment of significant positive effect on the motivation of auditors. While the change in authority but not significant positive effect on the motivation of auditors.Keywords: audit fees, competence, organizational commitment, professional commitment, changes in authority, and motivation of auditors